Social identification in groups - Thye, Shane R.; Lawler, Edward J. (Advances in group processes ;, 2005)
Advances in Group Processes publishes theoretical analyses, reviews and theory based empirical chapters on group phenomena. Volume 22, the fourth volume of a 5-series set, includes papers that address fundamental issues of Social Identification in Groups. Chapter one examines how group identities can have beneficial and detrimental effects on workplace commitment. The second chapter examines the emotional reactions that emerge when transient meanings do not match the meaning of ones identity standard. The third chapter uses identity theories to understand how performance on an academic test is impaired when scoring well on the test is not consistent with the identity. As a group, these three chapters address new empirical and theoretical problems at the cutting edge of identity theory and research. The next three chapters take on issues of identity and social structure. Chapter four theorizes and tests a core idea in identity theory, that structural constraints and opportunities shape the development of commitments to social relations. The authors conduct a test of this claim using survey data from a five county region of southern California. The next chapter integrates status characteristics theory with principles from social identity theory to show how status structures and group membership combine to produce influence in task settings. Chapter six puts forward a theory of collective identity that addresses whether collective identities cause or are caused by participation in a social movements, and whether subgroup identities are inversely or positively related to larger group identities. The next two papers address issues of social identity and uncertainty. Chapter seven tests and supports the claim that people take longer to define the identity of androgynous looking individuals, and that their presence will slow performance on a cognitive task. Chapter eight examines the emergence of ideology in the context of theory and research on uncertainty, group identification, group prototypes and entitativity. The final chapter in the volume seeks to understand how multiple identity standards can be activated simultaneously, and how identity perceptions shift from members of separate groups to members of a single, more inclusive group. Overall, the volume includes papers that reflect a wide range of theoretical approaches to social identity and contributions by major scholars that work in the general area of group processes.